Fox baiting against Echinococcus multilocularis: Contrasted achievements among two medium size cities. - Comte, Sébastien; Raton, Vincent; Raoul, Francis; Hegglin, Daniel; Giraudoux, Patrick; Deplazes, Peter; Favier, Stéphanie; Gottschek, Déborah; Umhang, Gérald; Boué, Franck; Combès, Benoit (Preventive Veterinary Medicine, 2013)
International audience In Europe, most cities are currently colonized by red foxes (Vulpes vulpes), which are considered to be the main definitive host of the zoonotic cestode Echinococcus multilocularis. The risk of transmission to humans is of particular concern where high fox populations overlap with high human populations. The distribution of baits containing praziquantel has successfully reduced the infection pressure in rural areas and in small plots within large cities. The purpose of this study was to assess its efficiency in two medium size cities (less than 100,000 inhabitants) in areas of high human alveolar echinococcosis incidence. From August 2006 to March 2009, 14 baiting campaigns of praziquantel treatment were run in Annemasse and Pontarlier (Eastern France), each of which encompassed 33km(2), with a density of 40baits/km(2). The bait consumption appeared to be lower in strictly urban context compared to suburban areas (78.9% vs. 93.4%) and lower in Annemasse than in Pontarlier (82.2% vs. 89.5%). During our study, the prevalence of E. multilocularis, as assessed by EM-ELISA on fox faeces collected in the field in Annemasse, was lower within the treated area than in the rural control area. A "before/during" treatment comparison revealed a significant decrease of spring prevalence from 13.3% to 2.2%. No significant change in prevalence was detected in Pontarlier (stable prevalence: 9.1%) where the contamination of the treated area followed the temporal trend observed in the control area. There, a greater resilience of the parasite's life cycle, probably due to a strong pressure of recontamination from outside the treated area, may have counteracted the prophylaxis treatment. These contrasted outcomes suggest that the frequency of fox anthelmintic treatment should be adapted to the local situation.